A hot syngas purification system integrated with downdraft gasification of municipal solid waste - Chan, Wei Ping (2019)
Gasification of municipal solid waste (MSW) with subsequent utilization of syngas in gas engines/turbines and solid oxide fuel cells can substantially increase the power generation of waste-to-energy facilities and optimize the utilization of wastes as a sustainable energy resources. However, purification of syngas to remove multiple impurities such as particulates, tar, HCl, alkali chlorides and sulfur species is required. This study investigates the feasibility of high temperature purification of syngas from MSW gasification with the focus on catalytic tar reforming and desulfurization. Syngas produced from a downdraft fixed-bed gasifier is purified by a multi-stage system. The system comprises of a fluidized-bed catalytic tar reformer, a filter for particulates and a fixed-bed reactor for dechlorination and then desulfurization with overall downward cascading of the operating temperatures throughout the system. Novel nano-structured nickel catalyst supported on alumina and regenerable Ni-Zn desulfurization sorbent loaded on honeycomb are synthesized. Complementary sampling and analysis methods are applied to quantify the impurities and determine their distribution at different stages. Experimental and thermodynamic modeling results are compared to determine the kinetic constraints in the integrated system. The hot purification system demonstrates up to 90% of tar and sulfur removal efficiency, increased total syngas yield (14%) and improved cold gas efficiency (12%). The treated syngas is potentially applicable in gas engines/turbines and solid oxide fuel cells based on the dew points and concentration limits of the remaining tar compounds. Reforming of raw syngas by nickel catalyst for over 20 h on stream shows strong resistance to deactivation. Desulfurization of syngas from MSW gasification containing significantly higher proportion of carbonyl sulfide than hydrogen sulfide, traces of tar and hydrogen chloride demonstrates high performance of Ni-Zn sorbents.